2011
DOI: 10.1111/j.1742-1241.2011.02756.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual counselling of cardiac patients in Europe: culture matters

Abstract: Background: Sexual problems are common amongst cardiac patients, and concerns may arise

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 26 publications
2
29
2
1
Order By: Relevance
“…Amongst other healthcare professionals, nurses can play a significant role in conducting sexual health assessment [30]. Nurses have good relationships with patients due to their daily contact with patients that facilitate assessment of sexual health [31]. Moreover, nurses documented that sexual health assessment for patients is a part of their professional role [32].…”
Section: Sexual Health Assessment In Clinical Practicementioning
confidence: 99%
“…Amongst other healthcare professionals, nurses can play a significant role in conducting sexual health assessment [30]. Nurses have good relationships with patients due to their daily contact with patients that facilitate assessment of sexual health [31]. Moreover, nurses documented that sexual health assessment for patients is a part of their professional role [32].…”
Section: Sexual Health Assessment In Clinical Practicementioning
confidence: 99%
“…10Y12 Nurses play an important role in assisting patients adapt to their lifestyles and learn how to live with their illness, 4,13,14 which should include sexual counseling to HF patients. 3,15,16 In several European studies (eg, the Netherlands, Belgium, Denmark, and Ireland) and studies from the United States, the perceptions of cardiac nurses regarding their roles in discussing sexual concerns with their patients were described. 15,17Y21 Although most nurses in these studies reported feeling responsible for discussing sexual concerns, they rarely do so in daily practice.…”
mentioning
confidence: 99%
“…33,44,50 Only a few studies have focused on the number of patients receiving sexual counseling, 2,51 and even fewer have examined the quality and efficacy of sexual counseling after a cardiac event or stroke. 19,[52][53][54] Healthcare professionals must balance the sensitivity of the topic, their own knowledge and comfort, and the need for education and support on the part of the patient when discussing resumption of sexual activity.…”
Section: Patient Counselingmentioning
confidence: 99%
“…Cultural and language barriers may also inhibit sensitive discussions. 15,17,22,[32][33][34][35][36][37][38][39] Although healthcare professionals indicate some knowledge about sexual activity in cardiac populations and are willing to engage in sexual counseling, 22 evidence suggests limited follow-through in providing such interventions to patients 40,41 because of lack of confidence and specialized training, 15,32,42 as well as perceived restrictions in the practice setting 43 and cultural background of the healthcare provider. 33 Specific areas of knowledge to be addressed in staff training are the role of intimacy without sex to gain confidence, positions for sexual activity, use of foreplay before sexual activity, and avoidance of unfamiliar partners and surroundings, 17,36,44 as well as knowledge regarding the use of medications to enhance sexual performance and whether or not these are safe for patients to use with specific types of CVD.…”
Section: 171920mentioning
confidence: 99%